An Oncogenic ALK Fusion and an RRAS Mutation in KRAS Mutation‐Negative Pancreatic Ductal Adenocarcinoma - Shimada, Yoko (Oncologist, 2017)
PURPOSE. Oncogenic mutations in the KRAS gene are a well‐known driver event, occurring in >95% of pancreatic cancers. The objective of this study was to identify driver oncogene aberrations in pancreatic cancers without the KRAS mutation. METHODS. Whole‐exome and transcriptome sequencing was performed on four cases of KRAS mutation‐negative pancreatic ductal adenocarcinoma, which were identified in a cohort of 100 cases. RESULTS. One case harbored an oncogenic DCTN1‐ALK fusion. The fusion gene enabled interleukin‐3‐independent growth of Ba/F3 cells and rendered them susceptible to the anaplastic lymphoma kinase tyrosine kinase inhibitors crizotinib and alectinib. The structure of the breakpoint junction indicated that the fusion was generated by nonhomologous end joining between a segment of DCTN1 exon DNA and a segment of ALK intron DNA, resulting in the generation of a cryptic splicing site. Another case harbored an oncogenic RRAS mutation that activated the GTPase of the RRAS protein. CONCLUSION. Rare oncogenic aberrations, such as the ALK fusion and RRAS mutation, may drive pancreatic carcinogenesis independent of the KRAS mutation. IMPLICATIONS FOR PRACTICE. The oncogenic DCTN1‐ALK fusion and the RRAS mutation were associated with the development of pancreatic ductal adenocarcinoma (PDAC) in the absence of the KRAS mutation. Constitutional activation of DCTN1‐ALK fusion protein was suppressed by the anaplastic lymphoma kinase tyrosine kinase inhibitors crizotinib and alectinib. Thus, a small subset of PDAC patients might benefit from therapy using these inhibitors.